The Protective Effect of Cordycepin on D-Galactosamine/Lipopolysaccharide-Induced Acute Liver Injury - Jin Li; Liping Zhong; Haibo Zhu; Fengzhong Wang (Hindawi Limited, 2017)
As the major active ingredient of Cordyceps militaris, cordycepin (3'-deoxyadenosine) has been well documented to alleviate inflammation and oxidative stress both in vitro and in vivo. To explore the potential protective effect of cordycepin in fulminant hepatic failure, mice were pretreated with cordycepin for 3 weeks followed by D-galactosamine (GalN)/lipopolysaccharide (LPS) injection. Then we found cordycepin (200 mg/kg) administration elevated survival rate, improved liver function, and suppressed hepatocyte apoptosis and necrosis in mice with severe hepatic damage by GalN/LPS treatment. Further, cordycepin inhibited hepatic neutrophil and macrophage infiltration and prevented proinflammatory cytokine production possibly through suppressing TLR4 and NF-κB signaling transduction. The blockade of reactive oxygen species (ROS) and lipid peroxidation production by cordycepin was associated with the decrease of NAD(P)H oxidase (NOX) activity. Besides, cordycepin significantly prevented excessive autophagy induced by GalN/LPS in the liver. These data suggested that cordycepin could be a promising therapeutic agent for GalN/LPS-induced hepatotoxicity.